A negative electrode material and its preparation method and application
By loading red phosphorus between layers of hard carbon or porous graphite secondary particles, the problems of insufficient energy density and poor circulation stability of negative electrode materials in lithium-ion batteries and sodium-ion batteries are solved, and the volume suppression and conductivity of red phosphorus are achieved, which significantly improves the performance of the battery.
Patent Information
- Application Number
- CN202411935915.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-08
AI Technical Summary
The existing negative electrode materials have insufficient energy density, poor cycle stability and volume expansion problems in lithium-ion batteries and sodium-ion batteries, which are difficult to meet the needs of high energy density and long cycle life.
By loading red phosphorus between layers of hard carbon or graphite secondary particles with porous surfaces, the small radius characteristic of phosphorus atoms is used to bind red phosphorus between layers of graphite or hard carbon, suppressing the volume effect of red phosphorus and improving conductivity.
The red phosphorus effectively suppresses volume expansion, improves the conductivity and circulation performance of the negative electrode material, and improves the rate performance and charge and discharge cycle performance of the battery.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a negative electrode material and a preparation method and application thereof. Background Art
[0002] In the field of energy storage such as lithium-ion batteries and sodium-ion batteries, the search for high-performance negative electrode materials has always been the focus and hotspot of research. At present, there are many problems with commonly used negative electrode materials in practical applications. Although traditional graphite negative electrode materials have good conductivity, their theoretical specific capacity is relatively low, which makes it difficult to meet the growing demand for high energy density. As for hard carbon materials, although they have certain application potential in sodium-ion batteries, they also have problems such as insufficient energy density and poor cycle stability.
[0003] In the process of exploring ways to improve the performance of negative electrode materials, red phosphorus has attracted much attention due to its high specific capacity. The theoretical specific capacity of single red phosphorus is 2596mA·h / g, which is second only to silicon, and has the advantages of abundant reserves, low price, and non-toxicity. The theoretical specific capacity of the graphite negative electrode currently used in commercial lithium-ion batteries is 372mA·h / g, which is far lower than the theoretical specific capacity of red phosphorus. However, red phosphorus undergoes significant volume changes during the charge and discharge process, which leads to the destruction of the electrode structure, affects the cycle life and performance stability of the battery, and red phosphorus has poor conductivity. At the same time, the existing technology of compounding red phosphorus with graphite or hard carbon also has some defects. For example, the process in the compounding process is complicated, the cost is high, and it is difficult to achieve large-scale production. Moreover, the existing compounding methods often cannot effectively solve the volume expansion problem of red phosphorus, nor can they give full play to the good conductivity of graphite or hard carbon, so that the rate performance and charge and discharge cycle performance of the battery still need to be improved.
[0004] Therefore, there is an urgent need to find a negative electrode material that can compound red phosphorus with graphite or hard carbon to inhibit the volume effect of red phosphorus and improve the comprehensive performance of the negative electrode material to solve the above problems. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a negative electrode material that can well suppress the volume effect of red phosphorus, and can effectively improve the conductivity of the negative electrode material, and has good charge and discharge cycle performance and rate performance.
[0006] The invention also provides a method for preparing the negative electrode material.
[0007] The present invention also provides a negative electrode sheet comprising the negative electrode material.
[0008] According to an embodiment of the first aspect of the present invention, there is provided a negative electrode material, the negative electrode material comprising a carrier and red phosphorus loaded on the carrier;
[0009] The carrier is selected from hard carbon or graphite secondary particles with porous surfaces;
[0010] The loading amount b of the red phosphorus satisfies the relationship: 1.6a / m≤b≤4.8a / m, wherein m is the weight of the carrier, a is the porosity of the carrier, and a is 30% to 60%.
[0011] The negative electrode material according to the embodiment of the present invention has at least the following beneficial effects:
[0012] The negative electrode material of the present invention loads red phosphorus between the layers of hard carbon or graphite secondary particles with porous surfaces, and utilizes the smaller radius characteristic of phosphorus atoms to successfully bind the red phosphorus between the layers of graphite or hard carbon, effectively suppressing the volume effect of red phosphorus and effectively improving the conductivity of the negative electrode material. It has good charge and discharge cycle performance and rate performance, and has broad application prospects in the field of energy storage.
[0013] According to some embodiments of the present invention, the interlayer spacing d of the hard carbon is 002 It is 0.36~0.38nm.
[0014] According to some embodiments of the present invention, the aggregate particle size D50 of the hard carbon is 4-8 μm.
[0015] According to some embodiments of the present invention, the particle size of the hard carbon satisfies 2.5≤D90 / D10≤4.
[0016] According to some embodiments of the present invention, the porosity of the hard carbon is 40% to 60%.
[0017] When the carrier of the negative electrode material of the present invention is a composite of the hard carbon and red phosphorus mentioned above, the energy density of the sodium ion battery is significantly improved. Compared with a single hard carbon negative electrode, it has obvious advantages and provides a new solution for improving the performance of sodium ion batteries.
[0018] When the carrier of the negative electrode material of the present invention is a graphite secondary particle with a porous surface, it can be used in lithium-ion batteries. The pores and end faces of the graphite secondary particles facilitate the entry of phosphorus vapor into the graphite interlayer, avoiding direct contact between red phosphorus and the electrolyte. The presence of red phosphorus significantly increases the capacity and ED of the material, and the presence of graphite greatly improves the conductivity and dynamic performance of the material, and reduces the expansion of the material during the cycle process; the present invention uses the micropores and mesopores of graphite as channels for introducing red phosphorus into the graphite interlayer, which is beneficial to the loading of phosphorus element in the graphite interlayer and Li + The movement between layers further improves the rate performance of the material, while effectively alleviating the expansion of red phosphorus during the charging and discharging process.
[0019] According to some embodiments of the present invention, the interlayer spacing d of the graphite secondary particles is002 It is 0.335~0.345nm.
[0020] According to some embodiments of the present invention, the aggregate particle size D50 of the secondary graphite particles is 6.5-8.5 μm.
[0021] According to some embodiments of the present invention, the particle size of the secondary graphite particles satisfies 2.5≤D90 / D10≤4.
[0022] According to some embodiments of the present invention, the granulation degree r of the secondary graphite particles is finished product particle size / aggregate particle size=2-2.5.
[0023] According to some embodiments of the present invention, the porosity of the secondary graphite particles is 30% to 50%.
[0024] The graphite secondary particles selected by the present invention with specific porosity, particle size, interlayer spacing, and granulation degree contain more low-crystalline components and more micropores relative to the graphite primary particles, thereby increasing the material's gram capacity and reducing expansion. In addition, the graphite secondary particles also have the following advantages: improving the material's lithium storage capacity: the end faces and micropores account for a larger proportion, so that the micropores can store more lithium ions, greatly increasing the material's gram capacity; optimizing battery performance: shortening the ion diffusion path, achieving rapid charging and discharging, and improving rate performance; enhancing structural stability, reducing volume changes, extending the lithium battery cycle life, and reducing replacement frequency and cost; improving material properties: softening the graphite material and increasing the powder compaction density; relieving red phosphorus expansion and improving rate performance; enhancing stability: selecting strongly granulated secondary particles, increasing isotropy, increasing the OI value of graphite, relieving expansion, and improving battery performance stability.
[0025] According to an embodiment of the second aspect of the present invention, a method for preparing the negative electrode material is provided, and the steps of the preparation method include:
[0026] The red phosphorus is heated and converted into white phosphorus vapor by an evaporation-condensation method and adsorbed by the carrier, and the temperature is lowered to convert the white phosphorus adsorbed on the carrier into red phosphorus.
[0027] According to some embodiments of the present invention, the red phosphorus D50 particle size before heating is 600-1000 nm.
[0028] The radius of the phosphorus atom of submicron red phosphorus is smaller than that of lithium and sodium atoms, so it can be bound between the layers of graphite or hard carbon.
[0029] According to some embodiments of the present invention, the heating temperature is 450-500° C., and the heating time is 2-3 hours.
[0030] According to some embodiments of the present invention, the cooling is to reduce the temperature to 260-280° C. and maintain it for 17-20 hours.
[0031] According to an embodiment of the second aspect of the present invention, there is provided a negative electrode plate comprising the above-mentioned negative electrode material.
[0032] According to an embodiment of the third aspect of the present invention, there is provided a use of the above-mentioned negative electrode material in the preparation of a lithium ion battery or a sodium ion battery.
[0033] According to some embodiments of the present invention, when the carrier is selected from hard carbon, the negative electrode material is used in a sodium ion battery; when the carrier is selected from graphite secondary particles, the negative electrode material is used in a lithium ion battery.
[0034] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%.
[0035] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0037] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below by reference are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0038] In the description of the present invention, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention based on the specific content of the technical solution.
[0039] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0040] The hard carbon, graphite primary particles and graphite secondary particles used in the examples and comparative examples were purchased from BTR New Materials Group Co., Ltd., and the activated carbon was purchased from IMAI Environmental Protection Technology Co., Ltd.
[0041] Example 1
[0042] This embodiment provides a negative electrode material, and the negative electrode material has the following characteristics:
[0043] The support is selected from hard carbon, whose interlayer spacing d 002 : 0.37nm, D50 particle size: 6μm, D90 / D10=3.5, porosity a is 50%, and weight m is 4kg.
[0044] This embodiment also provides a method for preparing the above-mentioned negative electrode material, comprising:
[0045] The evaporation-condensation method is used to heat red phosphorus with a particle size of 800 nm to sublime and convert it into white phosphorus. The heating temperature is 470°C and the heating time is 2 hours. At this time, the phosphorus vapor is adsorbed by the carrier through capillary force and pressure difference, and then the temperature is lowered to 270°C to convert the white phosphorus into red phosphorus. The temperature is maintained for 18 hours, allowing the red phosphorus to enter the hard carbon layer from the pores on the surface of the carrier. The loading amount b of red phosphorus is 0.4 kg, satisfying 1.6a / m≤b≤4.8a / m.
[0046] Example 2
[0047] This embodiment provides a negative electrode material, which is different from the embodiment 1 in that the porosity a of the hard carbon is 40%, the weight m is 4 kg, and the rest is the same as the embodiment 1. Finally, the red phosphorus loading b of the negative electrode material prepared in the embodiment 2 is 0.31 kg, which satisfies 1.6a / m≤b≤4.8a / m.
[0048] Example 3
[0049] This embodiment provides a negative electrode material, which is different from the embodiment 1 in that the porosity a of the hard carbon is 60%, and the rest is the same as the embodiment 1. Finally, the red phosphorus loading b of the negative electrode material prepared in the embodiment 3 is 0.49 kg, which satisfies 1.6a / m≤b≤4.8a / m.
[0050] Example 4
[0051] This embodiment provides a negative electrode material, which is different from the embodiment 1 in that the carrier is selected from graphite secondary particles, and the interlayer spacing d 002 : 0.345nm, D50 particle size: 8.5μm, D90 / D10=4, granulation degree r is finished product particle size / aggregate particle size=2.5, porosity a is 50%, weight m is 4kg, and the rest is the same as Example 1. Finally, the red phosphorus loading b of the negative electrode material prepared in Example 4 is 0.42kg, satisfying 1.6a / m≤b≤4.8a / m.
[0052] Example 5
[0053] This embodiment provides a negative electrode material, which is different from the embodiment 1 in that the carrier is selected from graphite secondary particles, and the interlayer spacing d 002 : 0.335nm, D50 particle size: 6.5μm, D90 / D10=2.5, granulation degree r is finished product particle size / aggregate particle size=2, porosity a is 30%, weight m is 4kg, and the rest is the same as Example 1. Finally, the red phosphorus loading b of the negative electrode material prepared in Example 5 is 0.25kg, satisfying 1.6a / m≤b≤4.8a / m.
[0054] The preparation method of the negative electrode material in this embodiment is the same as that in embodiment 1.
[0055] Comparative Example 1
[0056] This comparative example provides a negative electrode material, which is different from Example 1 in that no red phosphorus is added, and the hard carbon of Example 1 is directly used as the negative electrode material.
[0057] Comparative Example 2
[0058] This comparative example provides a negative electrode material, which is different from Example 1 in that hard carbon with a porosity a of 20% is used as a carrier, and the rest is the same as Example 1. Finally, the red phosphorus loading b of the negative electrode material prepared in Comparative Example 2 is 0.07 kg.
[0059] Comparative Example 3
[0060] This comparative example provides a negative electrode material, which is different from Example 1 in that hard carbon with a porosity a of 70% is used as a carrier, and the rest is the same as Example 1. Finally, the red phosphorus loading b of the negative electrode material prepared in Comparative Example 3 is 0.62 kg.
[0061] Comparative Example 4
[0062] This comparative example provides a negative electrode material, which differs from Example 1 in that activated carbon with a porosity a of 40% is used as a carrier, and the weight m is 4 kg, and the rest is the same as Example 1. Finally, the red phosphorus loading b of the negative electrode material prepared in Comparative Example 4 is 0.3 kg.
[0063] Comparative Example 5
[0064] This comparative example provides a negative electrode material, which is different from Example 5 in that graphite secondary particles with a porosity a of 20% are used as carriers, and the rest are the same as Example 5. Finally, the red phosphorus loading b of the negative electrode material prepared in Comparative Example 5 is 0.09 kg.
[0065] Comparative Example 6
[0066] This comparative example provides a negative electrode material, which is different from Example 4 in that graphite secondary particles with a porosity a of 70% are used as carriers, and the rest are the same as Example 4. Finally, the red phosphorus loading b of the negative electrode material prepared in Comparative Example 6 is 0.5 kg.
[0067] Comparative Example 7
[0068] This comparative example provides a negative electrode material, which is different from Example 4 in that graphite primary particles are used as carriers, and the rest is the same as Example 4. Finally, the red phosphorus loading b of the negative electrode material prepared in Comparative Example 7 is 0.29 kg.
[0069] Comparative Example 8
[0070] This comparative example provides a negative electrode material, which is different from Example 4 in that no red phosphorus is added, and the graphite secondary particles of Example 4 are directly used as the negative electrode material.
[0071] Test Case
[0072] The negative electrode materials of Examples 1 to 3 and Comparative Examples 1 to 4 are prepared into negative electrode sheets according to conventional methods in the art, and then the negative electrode sheets, isolation films, and positive electrode sheets are stacked in order, so that the isolation films are placed between the positive and negative electrode sheets to play an isolating role, and then wound according to conventional methods to form bare cells; the bare cells are placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, formation, shaping and other processes, a sodium ion battery is obtained.
[0073] The negative electrode materials of Examples 4-5 and Comparative Examples 5 to 8 are prepared into negative electrode sheets according to conventional methods in the art, and then the negative electrode sheets, isolation films, and positive electrode sheets are stacked in order, so that the isolation films are placed between the positive and negative electrode sheets to play an isolating role, and then wound according to conventional methods to form bare cells; the bare cells are placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, formation, shaping and other processes, a lithium-ion battery is obtained.
[0074] The prepared sodium ion batteries and lithium ion batteries were subjected to the following performance tests:
[0075] Sodium electrode capacity test: Assemble the button cell (negative electrode shell - electrode piece - electrolyte - diaphragm - electrolyte - sodium piece - gasket - spring - positive electrode shell) for testing. First, let it stand for 12 hours, discharge at 0.1mA constant current to 5mV, let it stand for 10 minutes, then discharge at 0.05mA constant current to 5mV, let it stand for 10 minutes, then discharge at 0.005C constant current to 5mV, let it stand for 10 minutes, charge at 0.01mA constant current to 2V, and record the charging capacity.
[0076] Lithium battery gram capacity test: Assemble the button battery (negative electrode shell-electrolyte-diaphragm-electrolyte-lithium sheet-gasket-spring-positive electrode shell) for testing. First, discharge the battery to 5mV with a constant current of 0.1mA and let it stand for 10 minutes. Then discharge it to 5mV with a constant current of 0.05mA and let it stand for 10 minutes. Then charge it to 2.0V with a constant current of 0.1mA and record the charging capacity.
[0077] Lithium / sodium battery cycle capacity retention test: ① Charge the battery to 4.5V at 0.5C at 25℃, with a cutoff current of 0.05C and leave it for 5min; ② Measure the discharge capacity of the battery at this time, recorded as D before; ③ Discharge the battery to 3V at 0.8C and leave it for 5min; ④ Charge the battery to 4.5V at 1.5C, with a cutoff current of 0.05C and leave it for 5min; ⑤ Repeat the above steps ③ to ④ for 300 times and measure the discharge capacity of the battery at this time, recorded as D after; Calculate the cycle retention rate = D after / D before * 100%;
[0078] Cyclic expansion rate test of lithium battery / sodium battery: ① Charge the battery to 4.5V at 0.5C at 25℃, with a cut-off current of 0.05C, and let it sit for 5 minutes; ② Measure the thickness of the battery at this time, recorded as dbefore; ③ Discharge the battery to 3V at 0.8C, and let it sit for 5 minutes; ④ Charge the battery to 4.5V at 1.5C, with a cut-off current of 0.05C, and let it sit for 5 minutes; ⑤ Repeat the above steps ③ to ④ 300 times, then measure the thickness of the battery at this time, recorded as dbefore; Calculate the cyclic expansion rate = (dbefore-dbefore) / dbefore*100%.
[0079] Table 1 Performance test results
[0080]
[0081]
[0082] According to Table 1, in Example 1 and Example 2-3, the loading amount of red phosphorus increases, and the gram capacity is significantly improved, but the cycle capacity retention rate (fading) and cycle swelling rate (swelling) also change to a certain extent, but they are all within a reasonable range; compared with Example 1 and Comparative Example 1, when there is no red phosphorus loading, the gram capacity is very low, which is 300mAh / g of hard carbon, but the swelling is very small, which is due to the small swelling amount of hard carbon itself. Compared with Example 1 and Comparative Examples 2-3, when the red phosphorus loading amount of Comparative Example 2 is small, although the swelling and fading are not much different from Example 1, the gram capacity is small; when the loading amount of Comparative Example 3 is large, the fading and swelling worsen, which is because there is part of the red phosphorus on the surface of the hard carbon. Compared with Example 1 and Example 4, after the carrier is replaced with graphite, the advantages are maintained, but in sodium ion batteries, hard carbon is generally used as the negative electrode material because it is cheaper than graphite and has better energy density and cycle stability, so the subsequent comparative examples no longer compare the differences between graphite and hard carbon as carriers in sodium ion batteries.
[0083] Compared with Comparative Examples 5-6, Examples 4-5 have excessive porosity, and the red phosphorus loading will increase, but the red phosphorus will be exposed to the electrolyte environment, which will significantly deteriorate the capacity retention rate and expansion rate; while the capacity retention rate and expansion rate of the too low porosity are not significantly different from those of Example 1, but the gram capacity is greatly reduced. In Example 4 and Comparative Example 7, although the porosity of the primary graphite particles is the same as that of the secondary particles, the red phosphorus loading does not reach the level of the secondary particles. This is because the isotropy of the primary particles is poor, and the red phosphorus cannot enter the interior of the graphite from all angles; and the expansion rate does not reach the level of Example 4, which is also due to its poor isotropy and cannot relieve expansion at all angles. Compared with Comparative Example 8, Example 4 has no red phosphorus loading, and although the capacity retention rate is significantly improved, the gram capacity and ED are too low and are not within a reasonable range. Comparative Example 4 uses activated carbon, although there are many holes on the surface, but the activated carbon itself does not have the ability to store sodium / lithium, so its gram capacity is negligible; secondly, the activated carbon is fragile, and the structure is prone to collapse during the rolling process, resulting in the exposure of red phosphorus; it is also easy to fall off during the cycle, so that fading and swelling deteriorate significantly.
[0084] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A negative electrode material, characterized in that: The negative electrode material includes a carrier and red phosphorus loaded on the carrier; The carrier is selected from hard carbon or graphite secondary particles with porous surfaces; The red phosphorus loading b satisfies the relationship: 1.6a / m≤b≤4.8a / m, Wherein m is the weight of the carrier, a is the porosity of the carrier, and a is 30% to 60%.
2. The negative electrode material according to claim 1, characterized in that The interlayer spacing d of the graphite secondary particles 002 is 0.335-0.345 nm; and / or, the aggregate particle size D50 of the graphite secondary particles is 6.5-8.5 μm; and / or, the particle size of the graphite secondary particles satisfies 2.5≤D90 / D10≤4; and / or, the porosity of the graphite secondary particles is 30%-50%.
3. The negative electrode material according to claim 1 or 2, characterized in that: The granulation degree r of the graphite secondary particles is finished product particle size / aggregate particle size=2-2.
5.
4. The negative electrode material according to claim 1, characterized in that The interlayer spacing d of the hard carbon 002 is 0.36-0.38 nm; and / or, the aggregate particle size D50 of the hard carbon is 4-8 μm; and / or, the particle size of the hard carbon satisfies 2.5≤D90 / D10≤4; and / or, the porosity of the hard carbon is 40%-60%.
5. A method for preparing a negative electrode material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: The red phosphorus is heated and converted into white phosphorus vapor by an evaporation-condensation method and adsorbed by the carrier, and the temperature is lowered to convert the white phosphorus adsorbed on the carrier into red phosphorus.
6. The preparation method according to claim 5, characterized in that: The red phosphorus D50 particle size before heating is 600-1000nm.
7. The preparation method according to claim 5, characterized in that: The heating temperature is 450-500° C., and the heating time is 2-3 hours.
8. The preparation method according to claim 5, characterized in that: The cooling step is to reduce the temperature to 260-280° C. and maintain the temperature for 17-20 hours.
9. A negative electrode plate, characterized in that: The negative electrode material comprises the negative electrode material as claimed in any one of claims 1 to 4.
10. Use of the negative electrode material according to any one of claims 1 to 4 in the preparation of a lithium ion battery and / or a sodium ion battery.